Metallo-B-iactamase production by pseudomonas aeruginosa of septicemic patients - Al grawi, Ibtesam G.; Belal, Sabbah A.; Al-Abasli, Amera K. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: P. aeruginosa remains a important cause of life threatening bloodstream infection in immunocompromised patients, particularly those with hematologic malignancies complicated by neutropeni.